Management of chickpea root rot and collar rot by integration of biological and chemical seed treatment - A.N. MUKHOPADHYAY, A.K. TEWARI* and (Indian Phytopathology, 2003)
Biologically and chemically treated chickpea seeds observed after one month showed that vitavax (carboxin @ 1g-k9 seed) did not significantly affect the spore viability of Glioc/adium virens (Gv). Application of carboxymethyl cellulose (CMC) with G.virens powder (109 spores-9) in combination with vitavax provided maximum protection (81.9%) to the crop against chickpea root rot and collar rot pathogens in glasshouse. Chickpea seeds treated with Gv powder+ CMC+vitavax significantly increased seedling emergence (47.9%); final plant stand (85.8%) and grain yield (79.7%) which was statistically at par with the treatment Gv powder+vitavax and Gv suspension + vitavax in a sick plot.